Educational Institutions' Strategies and Innovations to Improve the Teachers' Quality in Pandemic Situation - Aziz, Su’udin; Isroani, Farida (Universitas Muhammadiyah Sidoarjo, 2022)
This research aims to investigate the role of educational institution strategy and innovation in improving the quality of education. This investigation is qualitative and descriptive by nature. According to the findings of the study, the strategy of educational institutions during the pandemic, for instance, is based on the existence of a principal-designed program. The objective of executing the program is to increase the quality of teachers in both the present and the future. These activities take the form of seminars, microteaching, and book reviews. This activity has a positive effect on the quality of teachers in school institutions, as indicated by a rise in the personality, knowledge, and social standing of each teacher, which has an effect on the learning process offered by teachers during the pandemic. During the COVID-19 pandemic, several measures and innovations were used to enhance the quality of the institution's human resources. While the intention of this study was to determine the tactics and innovations implemented to improve the quality of teachers during the COVID-19 pandemic, it also aimed to assess the effectiveness of these strategies and innovations. This research may be utilized as a guide by other institutions to improve the quality of teachers in any context or circumstance, including the present COVID-19 pandemic.